Pollution Status and the Annual Variations of Heavy Metals in the Surface Sediments of the Shacheng Port Dumping Area - CHEN Yong; WEN Dong; LAN Wangrong; LI Yun; HUANG Wen; YU Qiaoyan (Haiyang Kaifa yu guanli)
The content of heavy metals in surface sediments in the dumping area of Shacheng harbor was analyzed. The contents of Hg, As, Cu, Pb, Cd, Cr, Zn, sulphide and organic carbon all meet the quality standard of the first kind of marine sediments. Principal component analysis shows that the distribution of heavy metals in surface sediments in the dumping area of Shacheng port is greatly affected by the external dumping. The potential ecological risk index method was used to assess the ecological risk. The results showed that the dumping area of Shacheng harbor was polluted by Cd to a certain extent, and the Cd content in the investigated area had reached the moderate harm degree. The results of this study provide a basis for the scientific decision-making of the management departments in the dumping area of Shacheng port.